THE RELATIONSHIP BETWEEN HEALTH EXPENDITURES AND HUMAN DEVELOPMENT INDEX IN E-7 COUNTRIES: FOURIER APPROACH (Third Sector Social Economic Review, 2021)
Macroeconomic developments in the E-7 countries, which have a significant size in the global economy, attract the attention of researchers. The subject of this study is to examine whether there is a relationship between the health expenditures in these countries and the human development index, and if there is, the direction of this relationship. In this study, the relationship between health expenditures and human development index in E-7 countries is examined using annual data for the period 2000-2018. Panel LM unit root test with breaks, panel Fourier cointegration test and panel Fourier causality test are used in the analyses. As a result of the cointegration test, it has been determined that there is a long-term relationship between health expenditures and the human development index. The causality test results show that there is a causality relationship from health expenditures to the human development index for Mexico, and from the human development index to health expenditures for India.
Keywords: E-7 Countries; Panel Fourier Cointegration; Panel Fourier Causality